Evaluating the role of anti-corruption Authority’s in Tunisia After the issuance of the administrative reconciliation law - ghaboli, mouna (The journal of Teacher Researcher of Legal and political Studies, 2024)
Several anti-corruption bodies were established in Tunisia after the 2011 revolution, such as the Commission of Inquiry on Corruption and Bribery, the Good Governance and Anti-Corruption Commission, which the constitution called the National Anti-Corruption Commission, and the Truth and Dignity Commission, all of which attempt to achieve the revolution’s goals of fair development and an equal distribution of wealth among all Citizens and combating all forms of corruption and bribery in order to implement transitional justice to rebuild the Tunisian national system. However, the Parliament's adoption of the Administrative Reconciliation Law, which exempts some of those involved in corruption cases on the condition that they cooperate with the state, some believe that it conflicts with the work of the aforementioned bodies and undermines their effectiveness in achieving deterrence in the future. This makes us wonder about the effectiveness of the Tunisian anti-corruption authorities in reducing it, and the extent of the impact of the Tunisian Reconciliation Law on their work.